Bias, Knowledge, Skepticism, and Disagreement: Précis of Part iii of Bias: A Philosophical Study - Kelly, Thomas (International journal for the study of skepticism, 2024)
The third and final part of Bias: A Philosophical Study explores the connections between bias and some of the central topics of epistemology, including knowledge, skepticism, and disagreement. It defends the possibility of biased knowing: biased believers can sometimes know, even when they believe in accordance with their biases, and even if those biases guarantee that they would believe as they do even if the truth were otherwise. It argues that the possibility of biased knowing has significant implications for both philosophical methodology and traditional forms of skepticism. Extended consideration is given to the question of whether those of us who robustly favor our ordinary commonsense views over the possibilities that the skeptic calls to our attention are biased against skepticism in any objectionable sense. Finally, it critically examines our tendency to attribute bias to others in response to interpersonal disagreement and the epistemological significance of “the bias blind spot.”